Baby corn production and utilization of remaining fodder in total mixed ration of buffalo calves - BAKSHI, M P S; WADHWA, M; KUMAR, BALWINDER (The Indian Journal of Animal Sciences, 2021)
This study was taken up to find out suitable maize variety cultivated with or without fertilizer for baby corn ear production and evaluation of leftover fodder/green stalks as livestock feed. Experiment-1: Six varieties of hybrid maize [PMH-1 grain (V1), Bulland (V2), African Tall (V4), Dekalb 7074 Monsanto (V5), Proagro 4640 (V6), Egyptian variety G-5414 (V7)] and one composite maize variety J1006 (V3) were cultivated without fertilizer (F1), with either Azotobacter treated seed (F2), recommended dose of fertilizer (F3), or F2 + F3 (F4) at the University Farm. Experiment-2: The leftover fodder of the best baby corn hybrid variety and that from V3 were evaluated in total mixed ration (TMR) as feed for buffalo calves. In Experiment-1 the weight of edible cob without husk and fodder yield were the highest (P